Concomitant transcatheter occlusion versus thoracoscopic surgical clipping for left atrial appendage in patients undergoing ablation for atrial fibrillation: A meta-analysis - Zhang, Shijie; Cui, Yuqi; Li, Jinzhang; Tian, Hongbo; Yun, Yan; Zhou, Xiaoming; Fang, Hui; Zhang, Haizhou; Zou, Chengwei; Ma, Xiaochun (Frontiers in Cardiovascular Medicine, 2022)
Background: Both catheter left atrial appendage occlusion combined with ablation (COA) and thoracoscopic surgical left atrial appendage clipping combined with ablation (TCA) have shown favorable outcomes in management of patients with atrial fibrillation (AFib). However, studies comparing the endpoints of both techniques are still lacking. Herein, a meta-analysis of safety and efficacy outcomes of COA versus TCA was performed in patients with AFib. Methods: Pubmed, Embase, Cochrane, and Web of Science databases were searched for retrieving potential publications. The primary outcome was the incidence of stroke during follow-up period of at least 12 months. Secondary outcomes were acute success rate of complete left atrial appendage (LAA) closure by COA or TCA, postprocedural mortality and complications, and all-cause mortality during follow-up period of at least 12 months. Results: 19 studies of COA containing 1,504 patients and 6 studies of TCA with 454 patients were eligible for analysis. No significant difference in stroke and all-cause mortality was found in patients undergoing COA versus TCA after at least a 12-month follow-up (stroke: p=0.504; all-cause mortality: p=0.611). COA group had a higher acute success rate compared with TCA group (p=0.001). COA placed the patients at a higher risk of hemorrhage during the postprocedural period compared with TCA (p=0.023). A similar risk of other postprocedural complications (stroke/transient ischemic attack and pericardial effusion) and mortality was found in the COA group in comparison with TCA group (p>0.05). Conclusions: This meta-analysis showed that COA and TCA did not differ in stroke prevention and all-cause mortality in patients with AFib after a follow-up of at least 12 months. Postprocedural complications and mortality were almost comparable between the two groups. In the near future, high-quality randomized controlled trials exploring the optimal surgical strategies for AFib and endpoints of different procedures are warranted.